Health Aspects of Amateur Long-Distance Running - Damian Ruta; Bogumił Bocianiak; Anna Kajka; Julia Hamerska; Joanna Antczak; Laura Hamerska; Urszula Fenrych; Karolina Wojtczak; Olga Skupińska; Julia Lipska (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Running, as a generally accessible form of physical activity, is recognized as a popular means of preventing lifestyle diseases. Each year, an increasing number of people of various ages, levels of training, and physical fitness participate in mass running events. Purpose: The study aims to identify the opinions of amateur long-distance runners regarding health. Material: 140 individuals from several Polish provinces, approximately 30 years old. Method: A proprietary questionnaire survey. Results: The most important factor motivating the respondents to engage in long-distance running is the improvement of sports performance, followed by the need to relieve stress, improve quality of life, and, to a lesser extent, health goals. According to most respondents, endurance-based long-distance running is healthy because it improves physical fitness, positively affects the cardiovascular and respiratory systems, enhances immunity, and is a way to relieve stress. Only a few respondents believe that running is not healthy. The main forms of preparation for half marathons and marathons among runners include warm-up exercises before the planned effort and strength and muscle stretching exercises. In the studied group of runners, past injuries do not diminish the satisfaction of engaging in long-distance running. Despite a significant number of respondents having experienced injuries in the past while practicing this sport, they still consider running to be healthy. Conclusions: Long-distance running brings numerous health benefits. It improves physical fitness, positively affects cardiovascular function, including lowering blood pressure, significantly enhances sleep quality, and helps reduce stress, as confirmed by the respondent's opinions.